2017
DOI: 10.1177/1065912917744896
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Apportionment on Quality Candidate Emergence and Electoral Competition

Abstract: The U.S. apportions congressional districts both across states and within states based upon population. Scholars have long focused on the electoral implications of redistricting within states, but there has been less consideration of the electoral implications of apportionment across states. In this paper, I analyze congressional elections from 2002 to 2014 and theorize that the limited number of political opportunities in states with few congressional districts will lead to higher levels of quality candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This indirect effect is greater for economic performance because it is less volatile than presidential approval. Several studies have found candidate quality helps explain U.S. legislative election outcomes (Ban, Llaudet, and Snyder 2016; Carson, Engstrom, and Roberts 2007; Carson and Sievert 2017; Gaddie, Bullock, and Buchanan 1999; Geras 2018).…”
Section: Midterm Election Seat Lossmentioning
confidence: 99%
“…This indirect effect is greater for economic performance because it is less volatile than presidential approval. Several studies have found candidate quality helps explain U.S. legislative election outcomes (Ban, Llaudet, and Snyder 2016; Carson, Engstrom, and Roberts 2007; Carson and Sievert 2017; Gaddie, Bullock, and Buchanan 1999; Geras 2018).…”
Section: Midterm Election Seat Lossmentioning
confidence: 99%